(untitled) (Bangladesh Journal of Scientific Research, 2014)
Bangladesh Demographic and Health Survey data were used for the study. The results suggest that women in the East have an average of 2.34 living children compared to an average of 1.83 living children in the West. Women with all living female children are two times more likely to give births than women having at least one male child in the East. Sex preference is an important determinant of current use of contraception in Bangladesh. In the East, women with two sons are 1.9 times more likely to use contraception than women with two daughters. Current use of contraception divides the East and West for fertility differential. It also implies that the reduction in fertility may largely depend on increased use of effective birth control methods in future in Bangladesh. DOI: http://dx.doi.org/10.3329/bjsr.v26i1-2.20229 Bangladesh J. Sci. Res. 26(1-2): 37-46, December-2013